A cuproptosis and copper metabolism–related gene prognostic index for head and neck squamous cell carcinoma - Zhang, Shuaiyuan; Zhang, Lujin; Lu, Huanzi; Yao, Yihuan; Liu, Xiaoyong; Hou, Jingsong (Frontiers in Oncology, 2022)
Abstract Background: The aim of this study was to identify the prognostic value of cuproptosis and copper metabolism-related genes, to clarify its molecular and immunological characteristics, and to elucidate its benefits in head and neck squamous cell carcinoma (HNSCC). Methods: Details of human cuproptosis and copper metabolism-related genes were obtained from the msigdb database and the latest literature. The least absolute shrinkage and selection operator (LASSO) regression was used to identify prognostic genes associated with cuproptosis and copper metabolism, and this coefficient was used to construct a prognostic risk score model. The samples were divided into high-risk group and low-risk group according to the median risk score. Afterward, the molecular and immune characteristics and the benefit of this genes in HNSCC were analyzed. Results: The 14-gene signature was constructed to classify patients into low-risk and high-risk groups according to risk level. In the TCGA cohort, the overall survival rate (OS) of the high-risk group was lower than that of the low-risk group (P < 0.0001). The good performance of the gene signature for predicting OS was evaluated by area under the curve (AUC) of time-dependent ROC curves achieved 0.75 at 1 years, and 0.75 at 3 years, and 0.65 at 5 years. Similar performance had been demonstrated in external validation queues. GO, KEGG enrichment assays and PPI protein networks had been used to explore signaling pathways and potential mechanisms that were significantly active in patients with HNSCC. Besides, the 14 prognostic genes were significantly correlated with immune microenvironment, implying the possible involvement of these genes in the immunoregulation and development of HNSCC. Conclusions: Our results emphasize the significance of cuproptosis and copper metabolism as a predictive biomarker for HNSCC, and its expression levels seem to be correlated with immune related features, thus may be a promising biomarker for HNSCC prognosis.